Performance Measurement for “Es Puter Bang Karim” Use Supply Chain Operation Reference - Christofora Desi Kusmindari (International Journal of Informatics and Communication Technology (IJ-ICT), 2015)
“Es puter Bang Karim “ is the one company that produces ice cream in the city of Palembang . This company does not have a good performance measurement . Performance measurement systems in use today are not able to measure the actual value of the company's performance , because the valuation is only based on the perspective of the production output . supply chain operations reference is one of the performance measurement tool used to streamline material and machinery . Supply chain operations reference is considered more complete , systematic and more integrated . The purpose of this study was to determine the value of the performance of companies using supply chain operations reference . Results of this experiment showed that the value of the highest performance occurred in June with a value indicator ( 60.3 ) and lowest values in April with a value of ( 58.2 ) so that the average indicator 59.3 . This value includes the category average performance indicators . Need to improve performance in order to better index future.